Pubertal maturation, hormonal levels and body composition in Canadian male and female gymnasts - Klentrou, P.; Flouris, A.; Plyley, M. (Pre-olympic Congress 2004. Thessaloniki, Grécia. de 6 a 11 de Agosto de 2004, 2004)
The purpose of this study was to assess sexual maturation, hormonal levels, and body fat among competitive male and female Canadian gymnasts compared to a non-training control group.